Analysis of Internal Forces and Structural Dimensions on the Variations of Courtroom Placement of DPRK Building - Bermansyah, Surya; Meutia Shafwina, Yasmin; Hayati, Yulia (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2023)
The construction of state buildings is caused by the increased mobility of needs. One of them is the DPRK building that wants the placement of the plenary session room to be on the 2nd or 3rd floor. This study aims to evaluate the internal style and behavior of the structure that arises due to variations in the placement of the plenary session room so as to produce the most optimal choice of courtroom for the most effective structural dimensions. Structural analysis was carried out using the ETABS program by carrying out 4 variations of courtroom placement, namely Varian 1 (the courtroom is located on the 1st floor), Varian 2 (2nd floor), Varian 3 (3rd floor), and Varian 4 (4th floor). Variant 2 (DED) is a reference sourced from the DED from the planning consultant. The seismic load analysis used is the method of Dynamic Analysis of Response Spectrum Variety. Parameters reviewed are internal forces (axial, normal, and moment) and structural behavior (story displacement, displacement between floors, nominal base shear forces, and vertical irregularities). The calculation analysis refers to the latest standards, namely SNI 1726:2019, SNI 1727:2020, and SNI 2847:2019. The results of this study indicate that the greatest internal force values occur in Variant 4. The level displacement and the displacement between floors increase in the variant with the smaller structural element dimensions. The level displacement of the X and Y axes has increased in Variant 3 and Variant 4, and has decreased in Variant 1. The nominal base shear force value has decreased for Variants 1, 3, and 4 against Variant 2 (DED) because it has smaller structural dimensions. . All modeling variants experienced soft stiffness irregularity type 1A, excessive soft stiffness irregularity type 1B, and heavy (mass) irregularity type 2. Variant 1 was chosen as the variant with the best courtroom placement, because it met the requirements for earthquake design.